The Power Analysis of Semiconductor Devices in Multi-Phase Traction Inverter Topologies Applicable in the Automotive Industry - Simcak, Jakub; Frivaldsky, Michal; Resutik, Patrik (Communications - Scientific Letters of the University of Zilina, 2024)
The article deals with the power analysis of semiconductor devices nowadays commonly used in perspective traction inverter topologies suitable for automotive industry applications. The power analysis is devoted to topologies, which are the Voltage Source Inverter (VSI) topology and perspective three-level alternatives, which are the Neutral Point Clamped (NPC) and T-type Neutral Point Clamped (T-NPC) traction inverter topologies. The main part of the power analysis of the proposed topologies is done on multi-phase versions (specifically six-phase). Mentioned topologies are modelled through the use of the simulation environment PLECS, while the focus is given on the accurate determination of semiconductor devices' power losses. Collected data of each analyzed topology are then processed using the MATLAB environment. The analysis of power parameters aims to find out which of the mentioned topologies achieves the highest efficiency as an VSI system at various power levels using the same input parameters.
Keywords: multi-phase traction inverter; multi-level traction inverter; VSI; NPC; T-NPC; power loss analysis